MgFe2O4/Biochar Composites for Visible-Light Photo-Fenton Treatment of Azo Dyes: Material Optimization Assisted by Decision Tree Analysis - Jandira Leichtweis; Ana C. Ferreira Piazzi Fuhr; Guilherme Luiz Dotto; Luis G. Ramírez Mérida; Elvis Carissimi; Mathias Ulbricht; Salatiel Wohlmuth Da Silva (Water, Air, & Soil Pollution, 2026)
The increasing release of synthetic dyes into aquatic systems represents a significant environmental concern due to their persistence, toxicity, and resistance to conventional treatment processes. In this study, MgFe 2 O 4 /biochar composites derived from waste coffee grounds were developed as sustainable materials for the removal of organic pollutants from water via a heterogeneous photo-Fenton process. The materials were synthesized and characterized using XRD, FT-IR, SEM, EDS, and band gap analysis, revealing that the incorporation of biochar enhances surface functionality and promotes efficient electron transfer. The performance of the composites was evaluated for the degradation of tartrazine (TZ) and methyl orange (MO), two widely used azo dyes frequently detected in wastewater. Among the tested compositions, MFO1BC1 achieved complete color removal (100%) of both dyes within 60 min, significantly outperforming pure MgFe 2 O 4 . This improvement can be attributed to the synergistic interaction between MgFe₂O₄ and biochar, which may contribute to improved active-site accessibility and could facilitate charge separation, thereby enhancing the photo-Fenton treatment efficiency. A decision tree (DT) model was used to assist in the interpretation of the experimental data and selection of the optimal composite composition. Reusability tests confirmed the stability of the catalyst over eight cycles, indicating its practical applicability for wastewater treatment systems. Radical scavenging experiments identified •OH and O 2 •⁻ as the main species possibly responsible for pollutant degradation. This study provides new insights into the use of biochar-based composites for environmental remediation, highlighting a low-cost, sustainable, and efficient strategy for the treatment of dye-contaminated water, with potential implications for large-scale wastewater management and pollution control.

Quantifying model error uncertainty in seismic assessment of unreinforced masonry buildings using the equivalent frame method - Mathias Haindl; Ian F. C. Smith; Katrin Beyer (Bulletin of Earthquake Engineering, 2026)

Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Marine and coastal protected areas in the Caribbean: Numbers, areal extent, distributions, no-take status, and management attributes - Mathias T. Cramer; Savanna N. Hearne; Kenyon C. Lindeman; Jeffrey Bernus; Evan Tuohy; Stacey Mac Donald; Ralph G. Turingan (Marine Policy, 2026)

Structure elucidation of leadbeaterin-1, an ichthyotoxin associated with fish-killing blooms of Chrysochromulina leadbeateri in Northern Norwegian fjords - Xinhui Wang; Anita Solhaug; Bruno C. Garrido; Elizabeth M. Mudge; Mathias Fon; Aaron J.C. Andersen; Ingunn A. Samdal; Bente Edvardsen; Charlotte H. Gotfredsen; Per Juel Hansen; Christopher O. Miles; Thomas O. Larsen (Harmful Algae, 2026)

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Bioenergetic trophic trade‐offs determine mass‐dependent extinction thresholds across the Cenozoic - Justin D. Yeakel; Matthew C. Hutchinson; Christopher P. Kempes; Paul L. Koch; Pedro D. S. Ugarte; Jacquelyn L. Gill; Mathias M. Pires (Ecology, 2026)
Body size constrains trophic interactions, shaping the feasibility of species' populations. Over macroevolutionary timescales, these constraints feed back to shape selection on body size and diet. We develop a bioenergetic, three‐level trophic framework—typical of terrestrial mammalian ecosystems—to explore how bioenergetic trade‐offs emerging from predator–prey interactions constrain coexistence. We show that interactions among predators, prey, and subsidies destabilize populations at both small and large sizes, matching observed limits to predator size and diet. These instabilities constrain coexistence and highlight a feasible predator size range of ca. 40–110 kg, spanning the mean size of terrestrial Cenozoic hypercarnivores. Finally, we show that decreased dietary selectivity confers a fitness advantage to larger carnivores that wanes at the largest sizes, aligning with diet estimates for contemporary and Pleistocene species. Our results underscore that ecological pressures emerging from trophic interactions, rooted in energetics, give rise to selective forces driving observed macroevolutionary patterns.

Food microstructure in the data science era: From images to values - Ria G. Rodriguez; Ina Folmer; Jens Saalbrink; Miek Schlangen; Diana Soto-Aguilar; Mathias P. Clausen; José C. Bonilla (Food Structure, 2026)

Beyond Climate Change: The Role of Integrated Soil Fertility Management for Sustaining Future Maize Yield in Sub‐Saharan Africa - Antoine Couëdel; Gatien N. Falconnier; Myriam Adam; Rémi Cardinael; Johan Six; Moritz Laub; Alex C. Ruane; Kenneth Boote; Eric Justes; Ward N. Smith; Anthony M. Whitbread; François Affholder; et al. (Global Change Biology, 2026)
Climate change is projected to exacerbate food insecurity in sub‐Saharan Africa (SSA) by reducing crop yields and soil fertility. Many climate change impact studies in SSA have overlooked long‐term effects of soil fertility on crop yield. We evaluated maize yields under different scenarios of soil fertility (using soil organic carbon as a proxy) and climate change (considering changes in temperature, rainfall, and CO 2 ) at four sites in SSA. Using an ensemble of 15 calibrated soil‐crop models, we found a strong consensus that, without fertilization, soil fertility declines over time, impacting maize yields more strongly than changes in temperature, rainfall, or CO 2 . The model ensemble indicated that when accounting for soil fertility changes, the yield benefits of combined application of organic and mineral inputs increase over time, even under climate change. These findings highlight the importance of considering long‐term change in soil fertility when assessing impacts of climate change and integrated nutrient management on crop production in SSA.

Bidirectional Effects of Sleep Deprivation Associated with Parkinson’s Disease on Behavior, Oxidative Stress, and Energy Metabolism in Male and Female Rats - Gisiane B. Mathia; Gabriel S. Mondo; Lucas C. Pedro; Flávia S. Niero; Nátalli R. Rocha; Laisa N. Santos; Letícia M. Leonardo; Josimar G. Pereira; Carolina G. Alano; Isabela S. Lemos; Khiany Mathias; Anita Dal Bó Tiscoski; et al. (Molecular Neurobiology, 2026)

The coupling between monsoon rainfall and Sea Surface Temperature in the subtropical South Atlantic during the Last Glacial Period - Lucas C. Vasconcelos; Francisco W. Cruz; Juan Pablo Bernal; Marília C. Campos; Patrícia Piacsek; José L. Campos; Haiwei Zhang; Nicolás Stríkis; Mathias Vuille; Giselle Utida; Christian Millo; R. Lawrence Edward; et al. (Global and Planetary Change, 2025)

Pressure-temperature-time deformation of an Ediacaran-Cambrian foreland fold-and-thrust belt: the Southern Espinhaço Front, Araçuaí Orogen - Henrique C. Joncew; Ginaldo A.C. Campanha; Melina C.B. Esteves; Frederico M. Faleiros; Leonardo E. Lagoeiro; Klaus Wemmer; Ruy A.C. Vasconcelos; Bruno V. Ribeiro; Mathias Hueck (Journal of Structural Geology, 2025)

Construction of a 3D trophoblast model and validation by triiodothyronine (T3) treatment - Mariana M. Lourenço; Bianca M. Gonçalves; Vinícius V. Peghinelli; Maria T. de Sibio; Ester M. Vieira; Helena P. Tilli; Paula B. Rocha; Regiane M.C. Olímpio; Igor C. Deprá; Lucas S. Mathias; Marna E. Sakalem; Carlos R. Padovani; et al. (Tissue and Cell, 2025)

Data processing and acquisition geometry impact the estimation of plant trait-based functional richness from airborne imaging spectroscopy - Marius Vögtli; Isabelle S. Helfenstein; Daniel Schläpfer; Meredith C. Schuman; Mathias Kneubühler; Alexander Damm (Remote Sensing of Environment, 2025)

Advances in optical microscopy for food structure characterization - Jose C. Bonilla; Matias A. Via; Jonathan Brewer; Mathias P. Clausen (Food Structure, 2025)

Quantifying microscopic droplets in colloidal systems through machine learning-based image analysis - Jens Saalbrink; Tricia Y.J. Loo; Julia Mertesdorf; Peidi Xu; Mie T. Pedersen; Mathias P. Clausen; Jose C. Bonilla (Food Hydrocolloids, 2025)

Caspases and brain-derived Neurotrophic Factor Levels and their Correlations with Psychiatric Symptoms in post-COVID-19 - Lia D. R. Broseghini; Camila O. Arent; Lucas C. Pedro; Laísa N. dos Santos; Flávia S. Niero; Gabriel S. Mondo; Amanda G. Bertollo; Maiqueli Eduarda D. Mingoti; Khyani Mathias; Lucineia G. Danielski; Tatiana Barichello; João Quevedo; et al. (Neurotoxicity Research, 2025)

Landscape-scale forest cover shapes the complexity of seed-dispersal networks in regenerating forest fragments - Robert Timmers; Marina C. Côrtes; Marijke van Kuijk; Guilherme G. Canassa; Romano Staneke; Fabiana S.O. Rosin; Maud P.J. van Hooff; Jorn J.H. Knuit; Mathias M. Pires; Merel B. Soons (Biological Conservation, 2025)

The importance of reactive silica for maintaining soil health - Jörg Schaller; Markus Kleber; Daniel Puppe; Mathias Stein; Michael Sommer; Matthias C. Rillig (Plant and Soil, 2025)
Background and aim Soil health is vital for the sustainability of ecosystem services such as food and fiber production, nutrient cycling and water supply. Soil health can be assessed through a combination of physical, biological and chemical metrics. There is emerging evidence that reactive silica is a strong factor controlling soil functions. Scope We explain how reactive silica, specifically dissolved silicic acid and amorphous silica, can be used as a new metric for assessing soil health, complementing traditional metrics or even substituting for them. Conclusion The pivotal role of reactive silica for soil health is particularly important under stress conditions that are typically associated with drought and soil degradation. The status of reactive silica indicates soil degradation earlier than the currently used metrics, because reactive silica depletion is followed by soil degradation. We recommend suitable methods and benchmarks for assessing reactive silica. Furthermore, we suggest further research to improve our understanding of the importance of reactive silica for soil health. We call upon the soil research community to include reactive silica as a metric for soil health assessment.

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

How does sensor-wise N-BANDS relate to the of area of feasible solutions? - Tomass Andersons; Alejandro C. Olivieri; Mathias Sawall; Martina Beese; Klaus Neymeyr (Analytica Chimica Acta, 2025)

Association between traumatic brain injury and risk of developing infections in the central nervous system and periphery - Cristiano Julio Faller; Amanda C. S. Kursancew; Beatriz Brandão Lima; Nicole Golombieski Duarte; Júlia Torcelli Noetzold; Natalli Studnicka; Khiany Mathias; Fabricia Petronilho; Emilio Luiz Streck; Jaqueline S. Generoso (Metabolic Brain Disease, 2025)

Comparative analysis of underwater acoustic propagation models: Evaluating the trade-off between accuracy and computational demands for coastal noise predictions - S. Wynn-Simmonds; C. Vincent; D. Mathias; G. Richard (Marine Pollution Bulletin, 2025)

Impact of absolute values and changes in meteorological and air quality conditions on community-acquired pneumonia in Germany - Saeed A. Khan; Thomas Brenner; Ann-Christine Link; Christoph Reudenbach; Jörg Bendix; Barbara C. Weckler; Max Kutzinski; Jan Rupp; Martin Witzenrath; Gernot Rohde; Mathias W. Pletz; Wilhelm Bertrams; et al. (International Journal of Biometeorology, 2025)
Community-acquired pneumonia (CAP) is a major global health concern as it is a leading cause of morbidity, mortality and economic burden to the health care systems. In Germany, more than 15,000 people die every year from CAP. Climate change is altering weather patterns, and it may influence the probability and severity of CAP. The increasing frequency and intensity of extreme weather events necessitate the study of their impact on CAP hospitalizations. In this regard, we examine the influence of absolute values and changes in various meteorological and air quality conditions on the frequency of CAP hospitalizations. We matched weather data to the German CAPNETZ-Cohort of 10,660 CAP patients from 22 healthcare facilities between 2003 and 2017. Our findings show that daily fluctuations in meteorological conditions (maximum temperature, 99th percentile precipitation), apart from relative humidity, are likely to result in triggering CAP hospitalizations than absolute conditions. In contrast, the absolute values of air quality (CO, NO 2 , O 3 , PM 2.5 , SO 2 , and total aerosols) are found to exert a greater influence on CAP hospitalizations than changes in air quality. The study outcomes have implications for public health measures, early warning systems, and public awareness, with the aim of mitigating the risk of CAP.

Using the ODD protocol and NetLogo to replicate agent-based models - Volker Grimm; Uta Berger; Justin M. Calabrese; Ainara Cortés-Avizanda; Jordi Ferrer; Mathias Franz; Jürgen Groeneveld; Florian Hartig; Oliver Jakoby; Roger Jovani; Stephanie Kramer-Schadt; Tamara Münkemüller; et al. (Ecological Modelling, 2025)

Effects of wholegrain pigmented rice on physical and nutritional properties of gluten-free bread - Gemaima C. Evangelista; Emanuel Steiger; Mathias Kinner; Henry Jäger; Regine Schönlechner (Journal of Cereal Science, 2025)

Feasible band boundaries computation in bilinear matrix decomposition using essential data - Somaye Vali Zade; Mathias Sawall; Klaus Neymeyr; Alejandro C. Olivieri; Roma Tauler; Hamid Abdollahi (Analytica Chimica Acta, 2025)

Soil Microbiome Inoculation for Resilient and Multifunctional New Forests in Post‐Agricultural Landscapes - Sofia I. F. Gomes; Per Gundersen; T. Martijn Bezemer; Davide Barsotti; Ludovica D'Imperio; Konstantinos Georgopoulos; Mathias Just Justesen; Karelle Rheault; Yamina M. Rosas; Inger Kappel Schmidt; Leho Tedersoo; Lars Vesterdal; et al. (Global Change Biology, 2025)
Afforestation is increasingly recognized as a critical strategy to restore ecosystems and enhance biodiversity on post‐agricultural landscapes. However, agricultural legacies, such as altered soil structure, nutrient imbalances, and depleted microbial diversity, can slow down forest establishment or cause ecosystems to deviate from expected successional trajectories. In this opinion paper, we explore the potential of soil inoculations as a tool to overcome these challenges by introducing beneficial microbial communities that can accelerate ecosystem recovery and forest development. Restoring soil biodiversity is a crucial aspect of this process that drives broader ecosystem functionality and resilience. We highlight the need to carefully consider the type and timing of inoculations and to ensure compatibility between the inoculum and recipient site characteristics to optimize the establishment of introduced species. While tree productivity is often a central focus of afforestation efforts, the restoration of soil biodiversity, which will also contribute to increased ecosystem‐level functions, should also be a priority for long‐term forest resilience. Agricultural legacies add complexities to the restoration process, creating unique challenges that need to be addressed in restoration planning. Thus, successful inoculation strategies require a thorough understanding of both donor and recipient site characteristics, also in relation to potential mismatches related to soil physiochemical properties to avoid unintended consequences such as the non‐establishment of introduced species. Additionally, we call for the re‐evaluation of afforestation targets and the development of standardized monitoring protocols that track the success of inoculation efforts, particularly regarding soil health, microbial community establishment, and biodiversity recovery. By integrating inoculation practices within a broader restoration framework, we can enhance the resilience, biodiversity, and ecosystem functionality of newly afforested landscapes. Ultimately, this approach may play a critical role in ensuring the success of large‐scale afforestation projects.

An almost infinite sites model - Alejandra Avalos-Pacheco; Mathias C. Cronjäger; Paul A. Jenkins; Jotun Hein (Theoretical Population Biology, 2024)

Mixed effect estimation in deep compartment models: Variational methods outperform first-order approximations - Alexander Janssen; Frank C. Bennis; Marjon H. Cnossen; Ron A. A. Mathôt; S. H. Reitsma; F. W. G. Leebeek; M. Coppens; K. Fijnvandraat; K. Meijer; S. E. M. Schols; H. C. J. Eikenboom; R. E. G. Schutgens; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
This work focusses on extending the deep compartment model (DCM) framework to the estimation of mixed-effects. By introducing random effects, model predictions can be personalized based on drug measurements, enabling the testing of different treatment schedules on an individual basis. The performance of classical first-order (FO and FOCE) and machine learning based variational inference (VI) algorithms were compared in a simulation study. In VI, posterior distributions of the random variables are approximated using variational distributions whose parameters can be directly optimized. We found that variational approximations estimated using the path derivative gradient estimator version of VI were highly accurate. Models fit on the simulated data set using the FO and VI objective functions gave similar results, with accurate predictions of both the population parameters and covariate effects. Contrastingly, models fit using FOCE depicted erratic behaviour during optimization, and resulting parameter estimates were inaccurate. Finally, we compared the performance of the methods on two real-world data sets of haemophilia A patients who received standard half-life factor VIII concentrates during prophylactic and perioperative settings. Again, models fit using FO and VI depicted similar results, although some models fit using FO presented divergent results. Again, models fit using FOCE were unstable. In conclusion, we show that mixed-effects estimation using the DCM is feasible. VI performs conditional estimation, which might lead to more accurate results in more complex models compared to the FO method.

Investigating the antibacterial potential of thiophene derivatives against wound infections: a combined DFT, molecular docking, and ADMET study targeting Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli resistant genes - Mathias O. Ajaba; Bassey E. Agbo; Nse Umoh; Ekaette S. Udoh; Alpha O. Gulack; Andrew Ushie; Friday O. Izachi; Bethel C. Ateb (In Silico Pharmacology, 2024)

The Rio de la Plata and Paranapanema cratons: Uncovering the hidden pieces of west Gondwana - Miguel A.S. Basei; Mathias Hueck; Sebastián Oriolo; Mario C. Campos Neto (Precambrian Research, 2024)

Effect of neonicotinoid and fungicide strobilurin in neotropical solitary bee Centris analis - Rafaela Tadei; Rebeca E.S. Castor; Osmar Malaspina; Elaine C. Mathias da Silva (Environmental Pollution, 2024)

Climatic variables influence the photosynthetic capacity of forest plantations in Brazil - Juscelina Arcanjo dos Santos; Otávio Camargo Campoe; Michael J. Aspinwall; Cléber Rodrigo de Souza; José Luiz Stape; Clayton A. Alvares; Joannès Guillemot; Guerric le Maire; Jean-Paul Laclau; Yann Nouvellon; Mathias Christina; Patricia Battie-Laclau; et al. (New Forests, 2024)

Using image-based inspection data to improve response predictions of earthquake-damaged unreinforced masonry buildings - Mathias Haindl; Ian F. C. Smith; Katrin Beyer (Bulletin of Earthquake Engineering, 2024)
Explicit representation of uncertainties is essential to improve the reliability of seismic assessments of earthquake-damaged buildings, particularly when dealing with unreinforced masonry buildings. Modern inspection techniques use images for detecting and quantifying the damage to a structure. Based on the principle of falsification, this paper evaluates how the use of information of damage that is obtained from images taken on earthquake-damaged buildings reduces the uncertainty when predicting the seismic response under a future earthquake. New model falsification criteria use information on the residual state of a building, such as shear cracks, residual roof displacements, and observation of out-of-plane failure. To demonstrate the effectiveness of these criteria in reducing the uncertainty in response predictions, results from a four-story unreinforced masonry building stiffened with reinforced concrete walls, which was experimentally tested under a sequence of ground motions, are assessed. Three commonly used modeling approaches (single degree of freedom (DOF) systems, multi DOF systems with four DOFs, and equivalent frame models) are used, where uncertainties in model parameters and model bias are included and propagated through the analysis. Out of the models used, and in the absence of any additional source of information, the proposed falsification criteria are most effective in connection with the equivalent frame model because this model can simulate the response at the element-level, while the simpler models can only represent the global response or the response at the storey-level. The results show that when using only the information on the presence of shear cracks, which might be the first and only source of information after an earthquake, the effectiveness of model falsification is increased, thus reducing the uncertainty in model parameter values and seismic response predictions through the use of image-based inspection.

Effects of the insecticide acetamiprid and the fungicide azoxystrobin on locomotion activity and mushroom bodies of solitary bee Centris analis - Rafaela Tadei; Claudia Inês da Silva; Elaine C. Mathias da Silva; Osmar Malaspina (Chemosphere, 2024)

Pan-African granitic magmatism of the Kaoko Belt: Tectonic perspective from its South American connection and insights into the crustal architecture of SW Gondwana - Mathias Hueck; Miguel A.S. Basei; Hartwig Frimmel; Lucas M. Lino; Vinicius X. Corrêa; Lucas R. Tesser; Mario C. Campos Neto; Carlos E. Ganade (Precambrian Research, 2024)

Africa Alive Corridors: Transdisciplinary Research based on African Footprints - B. Linol; M. Doucouré; J. Anderson; F. Toteu; W. Miller; P. Vale; P. Hoffman; G. I. H. Kerley; R. Auerbach; C. Thiart; M. Meghraoui; N. Dhliwayo; et al. (Geoheritage, 2024)
The idea of Africa Alive Corridors (AAC) evolved from Gondwana geological mapping to a comprehensive, more inclusive and dynamic approach to transdisciplinary research known as Earth Stewardship Science. Twenty designated corridors explore the geo-biological and cultural heritage of different regions of Africa over various periods, from deep time to the Anthropocene. Each corridor reveals a specific lens through which to investigate some of the rich scientific narratives embedded within it. The concept also facilitates learning and knowledge exchange across numerous disciplines: archeology, geology, geophysics, oceanography, glaciology, biology, botany, ecology, agriculture, engineering, spatial statistics, social sciences, and the humanities. This contribution analyses ten selected corridors in southern and western Africa, the Congo Basin, East Africa, and Madagascar. The various research themes explored include Earth impact hazard, origins of humankind, Snowball Earth, coastal food systems and conservation, the biogeography of lemurs, human settlement dynamics in Cameroon, tectonically linked earthquake occurrences in Algeria and Morocco, modelling land-use changes in the Western Rift Valley, trades and civilizations of the Mali Empire, Mbira music, and contemporary art. The ongoing work on these—and ten other—corridors has considerable potential to host new international collaborations to develop the links between society and natural sciences in Africa. Ultimately, AAC will benefit all stakeholders, especially the youth, in understanding and responding to societal needs and current global challenges.

Derivative-free search approaches for optimization of well inflow control valves and controls - Mathias C. Bellout; Thiago L. Silva; Jan Øystein Haavig Bakke; Carl Fredrik Berg (Computational Geosciences, 2024)
Decisions regarding problem conceptualization, search approach, and how best to parametrize optimization methods for practical application are key to successful implementation of optimization approaches within georesources field development projects. This work provides decision support regarding the application of derivative-free search approaches for concurrent optimization of inflow control valves (ICVs) and well controls. A set of state-of-the-art approaches possessing different search features is implemented over two reference cases, and their performance, resource requirements, and specific method configurations are compared across multiple problem formulations for completion design. In this study, problem formulations to optimize completion design comprise fixed ICVs and piecewise-constant well controls. The design is optimized by several derivative-free methodologies relying on parallel pattern-search ( t APPS), population-based stochastic sampling ( t PSO) and trust-region interpolation-based models ( t DFTR). These methodologies are tested on a heterogeneous two-dimensional case and on a realistic case based on a section of the Olympus benchmark model. Three problem formulations are applied in both cases, i.e., one formulation optimizes ICV settings only, while two joint configurations also treat producer and injector controls as variables. Various method parametrizations across the range of cases and problem formulations exploit the different search features to improve convergence, achieve final objectives and infer response surface features. The scope of this particular study treats only deterministic problem formulations. Results outline performance trade-offs between parallelizable algorithms ( t APPS, t PSO) with high total runtime search efficiency and the local-search trust-region approach ( t DFTR) providing effective objective gains for a low number of cost function evaluations. t APPS demonstrates robust performance across different problem formulations that can support exploration efforts, e.g., during a pre-drill design phase while multiple independent t DFTR runs can provide local tuning capability around established solutions in a time-constrained post-drill setting. Additional remarks regarding joint completion design optimization, comparison metrics, and relative algorithm performance given the varying problem formulations are also made.

The reorganization of predator–prey networks over 20 million years explains extinction patterns of mammalian carnivores - João C. S. Nascimento; Fernando Blanco; M. Soledad Domingo; Juan L. Cantalapiedra; Mathias M. Pires (Ecology Letters, 2024)
Linking the species interactions occurring at the scale of local communities to their potential impact at evolutionary timescales is challenging. Here, we used the high‐resolution fossil record of mammals from the Iberian Peninsula to reconstruct a timeseries of trophic networks spanning more than 20 million years and asked whether predator–prey interactions affected regional extinction patterns. We found that, despite small changes in species richness, trophic networks showed long‐term trends, gradually losing interactions and becoming sparser towards the present. This restructuring of the ecological networks was driven by the loss of medium‐sized herbivores, which reduced prey availability for predators. The decrease in prey availability was associated with predator longevity, such that predators with less available prey had greater extinction risk. These results not only reveal long‐term trends in network structure but suggest that prey species richness in ecological communities may shape large scale patterns of extinction and persistence among predators.

System shift in rice: Processes and pathways of change in rice-based production systems of Southeast Asia - Mathias Becker; Richelyn Clavero; Ohnmar Min Khin; Sichantha Kong; Zar Ni Maung; Punlork Men; Shyam Pariyar; Manuel José C. Regalado; Sophoanrith Ro; Kyaw Kyaw Win (Agricultural Systems, 2024)

Phase behaviour and structure formation of alginate-gelatin composite gels - Sabrina Bäther; Jasper Hartwig Seibt; Christoph Simon Hundschell; Jose C. Bonilla; Mathias Porsmose Clausen; Anja Maria Wagemans (Food Hydrocolloids, 2024)

Long-term soil organic carbon and crop yield feedbacks differ between 16 soil-crop models in sub-Saharan Africa - Antoine Couëdel; Gatien N. Falconnier; Myriam Adam; Rémi Cardinael; Kenneth Boote; Eric Justes; Ward N. Smith; Anthony M. Whitbread; François Affholder; Juraj Balkovic; Bruno Basso; Arti Bhatia; et al. (European Journal of Agronomy, 2024)

Understanding different dominance patterns in western Amazonian forests - Laura Matas‐Granados; Frederick C. Draper; Luis Cayuela; Julia G. de Aledo; Gabriel Arellano; Celina Ben Saadi; Timothy R. Baker; Oliver L. Phillips; Eurídice N. Honorio Coronado; Kalle Ruokolainen; Roosevelt García‐Villacorta; Katherine H. Roucoux; et al. (Ecology Letters, 2024)
Dominance of neotropical tree communities by a few species is widely documented, but dominant trees show a variety of distributional patterns still poorly understood. Here, we used 503 forest inventory plots (93,719 individuals ≥2.5 cm diameter, 2609 species) to explore the relationships between local abundance, regional frequency and spatial aggregation of dominant species in four main habitat types in western Amazonia. Although the abundance‐occupancy relationship is positive for the full dataset, we found that among dominant Amazonian tree species, there is a strong negative relationship between local abundance and regional frequency and/or spatial aggregation across habitat types. Our findings suggest an ecological trade‐off whereby dominant species can be locally abundant ( local dominants ) or regionally widespread ( widespread dominants ), but rarely both ( oligarchs ). Given the importance of dominant species as drivers of diversity and ecosystem functioning, unravelling different dominance patterns is a research priority to direct conservation efforts in Amazonian forests.

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Closing the gap between science and management of cold‐water refuges in rivers and streams - Francine H. Mejia; Valerie Ouellet; Martin A. Briggs; Stephanie M. Carlson; Roser Casas‐Mulet; Mollie Chapman; Mathias J. Collins; Stephen J. Dugdale; Joseph L. Ebersole; Danielle M. Frechette; Aimee H. Fullerton; Carole‐Anne Gillis; et al. (Global Change Biology, 2023)
Human activities and climate change threaten coldwater organisms in freshwater ecosystems by causing rivers and streams to warm, increasing the intensity and frequency of warm temperature events, and reducing thermal heterogeneity. Cold‐water refuges are discrete patches of relatively cool water that are used by coldwater organisms for thermal relief and short‐term survival. Globally, cohesive management approaches are needed that consider interlinked physical, biological, and social factors of cold‐water refuges. We review current understanding of cold‐water refuges, identify gaps between science and management, and evaluate policies aimed at protecting thermally sensitive species. Existing policies include designating cold‐water habitats, restricting fishing during warm periods, and implementing threshold temperature standards or guidelines. However, these policies are rare and uncoordinated across spatial scales and often do not consider input from Indigenous peoples. We propose that cold‐water refuges be managed as distinct operational landscape units, which provide a social and ecological context that is relevant at the watershed scale. These operational landscape units provide the foundation for an integrated framework that links science and management by (1) mapping and characterizing cold‐water refuges to prioritize management and conservation actions, (2) leveraging existing and new policies, (3) improving coordination across jurisdictions, and (4) implementing adaptive management practices across scales. Our findings show that while there are many opportunities for scientific advancement, the current state of the sciences is sufficient to inform policy and management. Our proposed framework provides a path forward for managing and protecting cold‐water refuges using existing and new policies to protect coldwater organisms in the face of global change.

Atlantic ITCZ variability during the Holocene based on high-resolution speleothem isotope records from northern Venezuela - N. Melissa M. Medina; Francisco W. Cruz; Amos Winter; Haiwei Zhang; Angela Ampuero; Mathias Vuille; Víctor C. Mayta; Marília C. Campos; Verónica Marcela Rámirez; Giselle Utida; Andrés Camilo Zúñiga; Hai Cheng (Quaternary Science Reviews, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

A linear SARS-CoV-2 DNA vaccine candidate reduces virus shedding in ferrets - Mathias Martins; Gabriela M. do Nascimento; Antonella Conforti; Jessica C. G. Noll; Joseph A. Impellizeri; Elisa Sanchez; Bettina Wagner; Lucia Lione; Erika Salvatori; Eleonora Pinto; Mirco Compagnone; Brian Viscount; et al. (Archives of Virology, 2023)

Revisiting Salvucci’s Semi-analytical Solution for Bare Soil Evaporation with New Consideration of Vapour Diffusion and Film Flow - Simon A. Mathias; Graham C. Sander; Jessica Leung; Samuel R. Newall (Transport in Porous Media, 2023)
Bare soil evaporation is controlled by a combination of capillary flow, vapour diffusion and film flow. Relevant analytical solutions mostly assume horizontal flow conditions and ignore gravitational effects. Salvucci (1997) provided a rare example of a semi-analytical solution for vertical bare soil evaporation. However, they did not explicitly represent vapour diffusion and film flow, which are likely to account for a significant proportion of total flow during vertical evaporation from soils. Vapour diffusion and film flow can be incorporated via Salvucci’s desorptivity parameter, which represents the proportionality constant relating Stage 2 cumulative evaporation to the square root of time under horizontal flow conditions. The objective of this article is to implement vapour diffusion and film flow within Salvucci’s semi-analytical solution and test its performance by comparison with isothermal numerical simulation and relevant experimental data. The following important conclusions are drawn. Analytical solutions that assume horizontal flow conditions are inadequate for understanding vertical evaporation problems because they overestimate evaporation rates and mostly predict vapour diffusion and film flow to be of negligible influence. Salvucci’s semi-analytical solution is effective at predicting the order-of-magnitude reduction in evaporation caused by gravitational effects. However, it is unable to identify the correct importance of vapour diffusion and film flow because these processes can only be represented through its desorptivity parameter.

Pan‐Arctic soil moisture control on tundra carbon sequestration and plant productivity - Donatella Zona; Peter M. Lafleur; Koen Hufkens; Beniamino Gioli; Barbara Bailey; George Burba; Eugénie S. Euskirchen; Jennifer D. Watts; Kyle A. Arndt; Mary Farina; John S. Kimball; Martin Heimann; et al. (Global Change Biology, 2023)
Long‐term atmospheric CO 2 concentration records have suggested a reduction in the positive effect of warming on high‐latitude carbon uptake since the 1990s. A variety of mechanisms have been proposed to explain the reduced net carbon sink of northern ecosystems with increased air temperature, including water stress on vegetation and increased respiration over recent decades. However, the lack of consistent long‐term carbon flux and in situ soil moisture data has severely limited our ability to identify the mechanisms responsible for the recent reduced carbon sink strength. In this study, we used a record of nearly 100 site‐years of eddy covariance data from 11 continuous permafrost tundra sites distributed across the circumpolar Arctic to test the temperature (expressed as growing degree days, GDD) responses of gross primary production (GPP), net ecosystem exchange (NEE), and ecosystem respiration (ER) at different periods of the summer (early, peak, and late summer) including dominant tundra vegetation classes (graminoids and mosses, and shrubs). We further tested GPP, NEE, and ER relationships with soil moisture and vapor pressure deficit to identify potential moisture limitations on plant productivity and net carbon exchange. Our results show a decrease in GPP with rising GDD during the peak summer (July) for both vegetation classes, and a significant relationship between the peak summer GPP and soil moisture after statistically controlling for GDD in a partial correlation analysis. These results suggest that tundra ecosystems might not benefit from increased temperature as much as suggested by several terrestrial biosphere models, if decreased soil moisture limits the peak summer plant productivity, reducing the ability of these ecosystems to sequester carbon during the summer.

Efficient well placement optimization under uncertainty using a virtual drilling procedure - Brage S. Kristoffersen; Thiago L. Silva; Mathias C. Bellout; Carl Fredrik Berg (Computational Geosciences, 2022)
An Automatic Well Planner (AWP) is used to efficiently adjust pre-determined well paths to honor near-well properties and increase overall production. AWP replicates modern geosteering decision-making where adjustments to pre-programmed well paths are driven by continuous integration of data obtained from logging-while-drilling and look-ahead technology. In this work, AWP is combined into a robust optimization scheme to develop trajectories that follow reservoir properties in a more realistic manner compared to common well representations for optimization purposes. Core AWP operation relies on an artificial neural network coupled with a geology-based feedback mechanism. Specifically, for each well path candidate obtained from an outer-loop optimization procedure, AWP customizes trajectories according to the particular geological near-well properties of each realization in an ensemble of models. While well placement searches typically rely on linear well path representations, AWP develops customized trajectories by moving sequentially from heel to the toe. Analog to realistic drilling operations, AWP determines subsequent trajectory points by efficiently processing neighboring geological information. Studies are performed using the Olympus ensemble. AWP and the two derivative-free algorithms used in this work, Asynchronous Parallel Pattern Search (APPS) and Particle Swarm Optimization (PSO), are implemented using NTNU’s open-source optimization framework FieldOpt. Results show that, with both APPS and PSO, the AWP solutions outperform the solutions obtained with a straight-line parameterization in all the three tested well placement optimization scenarios, which varied from the simplest scenario with a sole producer in a single-realization environment to a scenario with the full ensemble and multiple producers.

Differences in prey availability across space and time lead to interaction rewiring and reshape a predator–prey metaweb - Karoline Ceron; Diogo B. Provete; Mathias M. Pires; Andréa C. Araujo; Nico Blüthgen; Diego J. Santana (Ecology, 2022)
Space and time promote variation in network structure by affecting the likelihood of potential interactions. However, little is known about the relative roles of ecological and biogeographical processes in determining how species interactions vary across space and time. Here we study the spatiotemporal variation in predator–prey interaction networks formed by anurans and arthropods and test for the effects of prey availability in determining interaction patterns, information that is often absent and limits the understanding of the determinants of network structure. We found that network dissimilarity between ecoregions and seasons was high and primarily driven by interaction rewiring.We also found that species turnover was positively related to geographical distance. Using a null model approach to disentangle the effect of prey availability on the spatial and temporal variation, we show that differences in prey availability were important in determining the variation in network structure between seasons and among areas. Our study reveals that fluctuations in prey abundance, alongside the limited dispersal abilities of anurans and their prey, may be responsible for the spatial patterns that emerged in our predator–prey metaweb. These findings contribute to our understanding of the assembly rules that maintain biotic processes in metacommunities and highlight the importance of prey availability to the structure of these systems.

Invading the Occupied Niche: How a Parasitic Copepod of Introduced Oysters Can Expel a Congener From Native Mussels - Marieke E. Feis; Leo Gottschalck; Lena C. Ruf; Franziska Theising; Felicitas Demann; K. Mathias Wegner (Frontiers in Marine Science, 2022)
In species introductions, non-native species are often confronted with new niches occupied by more specialized natives, and for introduced parasites this conflict can be amplified because they also face novel hosts. Despite these obstacles, invasions of introduced parasites occur frequently, but the mechanisms that facilitate parasite invasion success are only rarely explored. Here, we investigated how the parasitic copepod Mytilicola orientalis , that recently spilled over from its principal host - the Pacific oyster Crassostrea gigas , managed to invade the niche of blue mussel Mytilus edulis intestines, which is densely occupied by its specialist congener, Mytilicola intestinalis . From field observations demonstrating invasion dynamics in nature, we designed a series of experiments addressing potential mechanisms facilitating a successful occupation of the new niche. As expected the specialist M. intestinalis can only infect mussel hosts, but displayed higher infection success there than M. orientalis in both principal host species combined. In the absence of direct competitive interactions M. orientalis compensated its lower infection success (1) by recurrent spill-over from its high-fitness reservoir oyster host, and (2) by active aggregation interference enhancing its own mating success while limiting that of M. intestinalis. The introduced parasite could thus avoid direct competition by changing its own epidemiology and indirectly decreasing the reproductive success of its competitor in the new host. Such mechanisms outside of direct competition have seldom been considered, but are crucial to understand invasion success, parasite host range and community assembly in the context of species introductions.

Madagascar Terrestrial Camera Survey Database 2021: A collation of protected forest camera surveys from 2007–2021 - Erin M. Wampole; Brian D. Gerber; Zach J. Farris; Jean Claude Razafimahaimodison; Mahandry Hugues Andrianarisoa; Claude Jacquot Ralazampirenena; Patricia C. Wright; C. Delaid Rasamisoa; Dean Gibson; Mathias W. Tobler; Timothy M. Eppley; Natalie Vasey; et al. (Ecology, 2022)
Madagascar is a threatened global biodiversity hotspot and conservation priority, yet we lack broad‐scale surveys to assess biodiversity across space and time. To fill this gap, we collated camera trap surveys, capturing species occurrences within Madagascar into a single standardized database. This data set includes nine distinct protected areas of Madagascar and encompasses 13 subprojects, 38 camera arrays, and 1156 sampling units (independent camera site per survey) within two important biodiversity eco‐regions: western dry deciduous forest and eastern humid rainforest. Camera surveys were conducted from June 2007 to January 2021. The final data set includes 17 unique families of mammals (Bovidae, Canidae, Cheirogaleidae, Daubentoniidae, Equidae, Eupleridae, Felidae, Hominidae, Indriidae, Lemuridae, Lepilemuridae, Muridae, Nesomyidae, Pteropodidae, Soricidae, Suidae, Tenrecidae) comprising 45 species and 27 unique families of birds (Accipitridae, Acrocephalidae, Alcedinidae, Bernieridae, Brachypteraciidae, Caprimulgidae, Cisticolidae, Columbidae, Coraciidae, Corvidae, Cuculidae, Dicruridae, Mesitornithidae, Monarchidae, Motacillidae, Muscicapidae, Numididae, Phasianidae, Rallidae, Sarothruridae, Strigidae, Sturnidae, Sulidae, Threskiornithidae, Upupidae, Vangidae, Zosteropidae) comprising 58 species. Images were processed and verified by individual project data set creators and camera operation and species tables were then collated. The final product represents the first broad‐scale freely available standardized formal faunal database for Madagascar. Data are available through this publication and at DOI: 10.5281/zenodo.5801806. These data will be useful for examining species‐level and community‐level trends in occurrence across space or time within Madagascar and globally, evaluating native and invasive species dynamics, and will aid in determining species conservation status and planning for at‐risk species. There are no copyright restrictions; please cite this paper when using the data for publication.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Early post-discharge mortality in CAP: frequency, risk factors and a prediction tool - Verena Glöckner; Mathias W. Pletz; Gernot Rohde; Jan Rupp; Martin Witzenrath; Grit Barten-Neiner; Martin Kolditz; M. Dreher; C. Cornelissen; W. Knüppel; D. Stolz; N. Suttorp; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
There are few data on mortality after discharge with community-acquired pneumonia (CAP). Therefore, we evaluated risk factors for 30-day post-discharge mortality after CAP. We included all patients of the prospective multi-national CAPNETZ study between 2002 and 2018 with (1) hospitalized CAP, (2) survival until discharge, and (3) complete follow-up data. The study endpoint was death within 30 days after discharge. We evaluated risk factors including demographics, comorbidities, admission CAP severity, and laboratory values and treatment-related factors in uni- and multivariable analyses. A total of 126 (1.6%) of 7882 included patients died until day 30 after discharge, corresponding to 26% of all 476 deaths. After multivariable analysis, we identified 10 independent risk factors: higher age, lower BMI, presence of diabetes mellitus, chronic renal or chronic neurological disease (other than cerebrovascular diseases), low body temperature or higher thrombocytes on admission, extended length of hospitalization, oxygen therapy during hospitalization, and post-obstructive pneumonia. By addition these factors, we calculated a risk score with an AUC of 0.831 (95%CI 0.822–0.839, p < 0.001) for prediction of post-discharge mortality. Early post-discharge deaths account for ¼ of all CAP-associated deaths and are associated with patient- and CAP-severity-related risk factors. Additional studies are necessary to replicate our findings in independent cohorts. Study registration: NCT 02139163.

Derivative-free trust region optimization for robust well control under geological uncertainty - Thiago L. Silva; Mathias C. Bellout; Caio Giuliani; Eduardo Camponogara; Alexey Pavlov (Computational Geosciences, 2022)
A Derivative-Free Trust-Region (DFTR) algorithm is proposed to solve the robust well control optimization problem under geological uncertainty. Derivative-Free (DF) methods are often a practical alternative when gradients are not available or are unreliable due to cost function discontinuities, e.g., caused by enforcement of simulation-based constraints. However, the effectiveness of DF methods for solving realistic cases is heavily dependent on an efficient sampling strategy since cost function calculations often involve time-consuming reservoir simulations. The DFTR algorithm samples the cost function space around an incumbent solution and builds a quadratic polynomial model, valid within a bounded region (the trust-region). A minimization of the quadratic model guides the method in its search for descent. Because of the curvature information provided by the model-based routine, the trust-region approach is able to conduct a more efficient search compared to other sampling methods, e.g., direct-search approaches. DFTR is implemented within FieldOpt, an open-source framework for field development optimization, and is tested in the Olympus benchmark against two other types of methods commonly applied to production optimization: a direct-search (Asynchronous Parallel Pattern Search) and a population-based (Particle Swarm Optimization). Current results show that DFTR has improved performance compared to the model-free approaches. In particular, the method presented improved convergence, being capable to reach solutions with higher NPV requiring comparatively fewer iterations. This feature can be particularly attractive for practitioners who seek ways to improve production strategies while using an ensemble of full-fledged models, where good convergence properties are even more relevant.

Cold-Air Pool Processes in the Inn Valley During Föhn: A Comparison of Four Cases During the PIANO Campaign - Maren Haid; Alexander Gohm; Lukas Umek; Helen C. Ward; Mathias W. Rotach (Boundary-Layer Meteorology, 2022)
We present a comprehensive analysis of four south föhn events observed during the Penetration and Interruption of Alpine Foehn (PIANO) field campaign in the Inn Valley, Austria, in the vicinity of Innsbruck. The goal is to detect and quantify processes of cold-air pool (CAP) erosion by föhn as well as processes of föhn breakdown. Despite differences in föhn breakthrough and strength, the four cases exhibit similarities in CAP evolution: initially, the CAP experienced strongest warming in the centre of Innsbruck, where the föhn jet from the Wipp Valley interacted with the CAP in the Inn Valley. The resulting shear-flow instability at the föhn–CAP interface caused turbulent CAP erosion and, together with vertical warm-air advection, led to CAP depression over the city centre. This depression drove pre-föhn westerlies near the surface that caused cold-air advection inside the CAP west of the city centre and warm-air advection in the east. Ultimately, the latter contributed to stronger CAP erosion in the east than in the west. This stronger heating also explains the preferential initial föhn breakthrough at the valley floor east of Innsbruck. In two of the cases, subsequent westward propagation of the föhn–CAP boundary across the city accompanied by northerly (deflected) föhn winds led to a complete föhn breakthrough. Föhn breakdown occurred either by a backflow of the CAP remnant or by a cold-frontal passage. This study emphasizes the importance of both turbulence and advection in the CAP heat budget and reveal their large spatio–temporal variability.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Disentangling the effect of climatic and hydrological predictor variables on benthic macroinvertebrate distributions from predictive models - Katie Irving; Sonja C. Jähnig; Mathias Kuemmerlen (Hydrobiologia, 2022)
Lotic freshwater macroinvertebrate species distribution models (SDMs) have been shown to improve when hydrological variables are included. However, most studies to date only include data describing climate or stream flow-related surrogates. We assessed the relative influence of climatic and hydrological predictor variables on the modelled distribution of macroinvertebrates, expecting model performance to improve when hydrological variables are included. We calibrated five SDMs using combinations of bioclimatic (bC), hydrological (H) and hydroclimatic (hC) predictor datasets and compared model performance as well as variance partition of all combinations. We investigated the difference in trait composition of communities that responded better to either bC or H configurations. The dataset bC had the most influence in terms of proportional variance, however model performance was increased with the addition of hC or H. Trait composition demonstrated distinct patterns between associated model configurations, where species that prefer intermediate to slow-flowing current conditions in regions further downstream performed better with bC–H. Including hydrological variables in SDMs contributes to improved performance, it is however, species-specific and future studies would benefit from hydrology-related variables to link environmental conditions and diverse communities. Consequently, SDMs that include climatic and hydrological variables could more accurately guide sustainable river ecosystem management.

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Windows of opportunity: Ocean warming shapes temperature‐sensitive epigenetic reprogramming and gene expression across gametogenesis and embryogenesis in marine stickleback - Alexandre Fellous; K. Mathias Wegner; Uwe John; Felix C. Mark; Lisa N. S. Shama (Global Change Biology, 2022)
Rapid climate change is placing many marine species at risk of local extinction. Recent studies show that epigenetic mechanisms (e.g. DNA methylation, histone modifications) can facilitate both within and transgenerational plasticity to cope with changing environments. However, epigenetic reprogramming (erasure and re‐establishment of epigenetic marks) during gamete and early embryo development may hinder transgenerational epigenetic inheritance. Most of our knowledge about reprogramming stems from mammals and model organisms, whereas the prevalence and extent of reprogramming among non‐model species from wild populations is rarely investigated. Moreover, whether reprogramming dynamics are sensitive to changing environmental conditions is not well known, representing a key knowledge gap in the pursuit to identify mechanisms underlying links between parental exposure to changing climate patterns and environmentally adapted offspring phenotypes. Here, we investigated epigenetic reprogramming (DNA methylation/hydroxymethylation) and gene expression across gametogenesis and embryogenesis of marine stickleback ( Gasterosteus aculeatus ) under three ocean warming scenarios (ambient, +1.5 and +4°C). We found that parental acclimation to ocean warming led to dynamic and temperature‐sensitive reprogramming throughout offspring development. Both global methylation/hydroxymethylation and expression of genes involved in epigenetic modifications were strongly and differentially affected by the increased warming scenarios. Comparing transcriptomic profiles from gonads, mature gametes and early embryonic stages showed sex‐specific accumulation and temperature sensitivity of several epigenetic actors. DNA methyltransferase induction was primarily maternally inherited (suggesting maternal control of remethylation), whereas induction of several histone‐modifying enzymes was shaped by both parents. Importantly, massive, temperature‐specific changes to the epigenetic landscape occurred in blastula, a critical stage for successful embryo development, which could, thus, translate to substantial consequences for offspring phenotype resilience in warming environments. In summary, our study identified key stages during gamete and embryo development with temperature‐sensitive reprogramming and epigenetic gene regulation, reflecting potential ‘windows of opportunity’ for adaptive epigenetic responses under future climate change.

An Automatic Well Planner for Complex Well Trajectories - Brage S. Kristoffersen; Mathias C. Bellout; Thiago L. Silva; Carl F. Berg (Mathematical Geosciences, 2021)
A data-driven automatic well planner procedure is implemented to develop complex well trajectories by efficiently adapting to near-well reservoir properties and geometry. The procedure draws inspiration from geosteering drilling operations, where modern logging-while-drilling tools enable the adjustment of well trajectories during drilling. Analogously, the proposed procedure develops well trajectories based on a selected geology-based fitness measure using an artificial neural network as the decision maker in a virtual sequential drilling process within a reservoir model. While neural networks have seen extensive use in other areas of reservoir management, to the best of our knowledge, this work is the first to apply neural networks on well trajectory design within reservoir models. Importantly, both the input data generation used to train the network and the actual trajectory design operations conducted by the trained network are efficient calculations, since these rely solely on geometric and initial properties of the reservoir, and thus do not require additional simulations. Therefore, the main advantage over traditional methods is the highly articulated well trajectories adapted to reservoir properties using a low-order well representation. Well trajectories generated in a realistic reservoir by the automatic well planner are qualitatively and quantitatively compared to trajectories generated by a differential evolution algorithm. Results show that the resulting trajectories improve productivity compared to straight line well trajectories, both for channelized and geometrically complex reservoirs. Moreover, the overall productivity with the resulting trajectories is comparable to well solutions obtained using differential evolution, but at a much lower computational cost.

Characterization of allelochemicals from Pistia stratiotes extracts and their effects on the growth and physiology of Microcystis aeruginosa - Anderson Lourenção; Gustavo F. Mecina; Micheline K. Cordeiro-Araújo; Maria C. Bittencourt-Oliveira; Mathias A. Chia; João L. Bronzel-Júnior; Filipe O. Granero; Luciana P. Silva; Regildo M. G. da Silva (Environmental Science and Pollution Research, 2021)

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

The Niederschlag fluorite-(barite) deposit, Erzgebirge/Germany—a fluid inclusion and trace element study - Sebastian Haschke; Jens Gutzmer; Cora C. Wohlgemuth-Ueberwasser; Dennis Kraemer; Mathias Burisch (Mineralium Deposita, 2021)
The Niederschlag fluorite-barite vein deposit in the Western Erzgebirge, Germany, has been actively mined since 2013. We present the results of a first comprehensive study of the mineralogy, petrography, fluid inclusions, and trace element geochemistry of fluorite related to the Niederschlag deposit. Two different stages of fluorite mineralization are recognized. Stage I fluorite is older, fine-grained, associated with quartz, and forms complex breccia and replacement textures. Conversely, the younger Stage II fluorite is accompanied by barite and often occurs as banded and coarse crystalline open-space infill. Fluid inclusion and REY systematics are distinctly different for these two fluorite stages. Fluid inclusions in fluorite I reveal the presence of a low to medium saline (7–20% eq. w (NaCl+CaCl 2 )) fluid with homogenization temperatures of 140–180 °C, whereas fluorite II inclusions yield distinctly lower (80–120 °C) homogenization temperatures with at least two high salinity fluids involved (18–27% eq. w (NaCl+CaCl 2 )). In the absence of geochronological data, the genesis of the earlier generation of fluorite-quartz mineralization remains enigmatic but is tentatively related to Permian magmatism in the Erzgebirge. The younger fluorite-barite mineralization, on the other hand, has similarities to many fluorite-barite-Pb-Zn-Cu vein deposits in Europe that are widely accepted to be related to the Mesozoic opening of the northern Atlantic Ocean.

Identifying dominant environmental predictors of freshwater wetland methane fluxes across diurnal to seasonal time scales - Sara H. Knox; Sheel Bansal; Gavin McNicol; Karina Schafer; Cove Sturtevant; Masahito Ueyama; Alex C. Valach; Dennis Baldocchi; Kyle Delwiche; Ankur R. Desai; Eugenie Euskirchen; Jinxun Liu; et al. (Global Change Biology, 2021)
While wetlands are the largest natural source of methane (CH 4 ) to the atmosphere, they represent a large source of uncertainty in the global CH 4 budget due to the complex biogeochemical controls on CH 4 dynamics. Here we present, to our knowledge, the first multi‐site synthesis of how predictors of CH 4 fluxes (FCH4) in freshwater wetlands vary across wetland types at diel, multiday (synoptic), and seasonal time scales. We used several statistical approaches (correlation analysis, generalized additive modeling, mutual information, and random forests) in a wavelet‐based multi‐resolution framework to assess the importance of environmental predictors, nonlinearities and lags on FCH4 across 23 eddy covariance sites. Seasonally, soil and air temperature were dominant predictors of FCH4 at sites with smaller seasonal variation in water table depth (WTD). In contrast, WTD was the dominant predictor for wetlands with smaller variations in temperature (e.g., seasonal tropical/subtropical wetlands). Changes in seasonal FCH4 lagged fluctuations in WTD by ~17 ± 11 days, and lagged air and soil temperature by median values of 8 ± 16 and 5 ± 15 days, respectively. Temperature and WTD were also dominant predictors at the multiday scale. Atmospheric pressure (PA) was another important multiday scale predictor for peat‐dominated sites, with drops in PA coinciding with synchronous releases of CH 4 . At the diel scale, synchronous relationships with latent heat flux and vapor pressure deficit suggest that physical processes controlling evaporation and boundary layer mixing exert similar controls on CH 4 volatilization, and suggest the influence of pressurized ventilation in aerenchymatous vegetation. In addition, 1‐ to 4‐h lagged relationships with ecosystem photosynthesis indicate recent carbon substrates, such as root exudates, may also control FCH4. By addressing issues of scale, asynchrony, and nonlinearity, this work improves understanding of the predictors and timing of wetland FCH4 that can inform future studies and models, and help constrain wetland CH 4 emissions.

Are visual working memory and episodic memory distinct processes? Insight from stroke patients by lesion-symptom mapping - Selma Lugtmeijer; Linda Geerligs; Frank Erik de Leeuw; Edward H. F. de Haan; Roy P. C. Kessels; Anouk R. Smits; Ben A. Schmand; Edward H. F. de Haan; Frank Erik de Leeuw; Gert jan Luijckx; H. Steven Scholte; Joke M. Spikman; et al. (Brain Structure and Function, 2021)
Working memory and episodic memory are two different processes, although the nature of their interrelationship is debated. As these processes are predominantly studied in isolation, it is unclear whether they crucially rely on different neural substrates. To obtain more insight in this, 81 adults with sub-acute ischemic stroke and 29 elderly controls were assessed on a visual working memory task, followed by a surprise subsequent memory test for the same stimuli. Multivariate, atlas- and track-based lesion-symptom mapping (LSM) analyses were performed to identify anatomical correlates of visual memory. Behavioral results gave moderate evidence for independence between discriminability in working memory and subsequent memory, and strong evidence for a correlation in response bias on the two tasks in stroke patients. LSM analyses suggested there might be independent regions associated with working memory and episodic memory. Lesions in the right arcuate fasciculus were more strongly associated with discriminability in working memory than in subsequent memory, while lesions in the frontal operculum in the right hemisphere were more strongly associated with criterion setting in subsequent memory. These findings support the view that some processes involved in working memory and episodic memory rely on separate mechanisms, while acknowledging that there might also be shared processes.

Effect of the hydroxamate group in the antitumoral activity and toxicity toward normal cells of new copper(II) complexes - Nathália F. B. Azeredo; Franz V. Borges; Marcelo S. Mathias; Jackson A. L. C. Resende; Roberto W. A. Franco; Milton M. Kanashiro; Adolfo Horn; Christiane Fernandes (BioMetals, 2021)

Forest responses to last‐millennium hydroclimate variability are governed by spatial variations in ecosystem sensitivity - Christine R. Rollinson; Andria Dawson; Ann M. Raiho; John W. Williams; Michael C. Dietze; Thomas Hickler; Stephen T. Jackson; Jason McLachlan; David JP Moore; Benjamin Poulter; Tristan Quaife; Jörg Steinkamp; et al. (Ecology Letters, 2021)
Forecasts of future forest change are governed by ecosystem sensitivity to climate change, but ecosystem model projections are under‐constrained by data at multidecadal and longer timescales. Here, we quantify ecosystem sensitivity to centennial‐scale hydroclimate variability, by comparing dendroclimatic and pollen‐inferred reconstructions of drought, forest composition and biomass for the last millennium with five ecosystem model simulations. In both observations and models, spatial patterns in ecosystem responses to hydroclimate variability are strongly governed by ecosystem sensitivity rather than climate exposure. Ecosystem sensitivity was higher in models than observations and highest in simpler models. Model‐data comparisons suggest that interactions among biodiversity, demography and ecophysiology processes dampen the sensitivity of forest composition and biomass to climate variability and change. Integrating ecosystem models with observations from timescales extending beyond the instrumental record can better understand and forecast the mechanisms regulating forest sensitivity to climate variability in a complex and changing world.

Reproductive biology of the anchovy (Stolephorus commersonnii, Lacepède, 1803) and spotted sardine (Amblygaster sirm, Walbaum, 1792) from Tanga Region, Tanzania - Joseph S. Sululu; Albogast T. Kamukuru; Baraka C. Sekadende; Shigalla B. Mahongo; Mathias M. Igulu (Western Indian Ocean Journal of Marine Science, 2021)
The present study investigated the reproductive biology of Stolephorus commersonnii and Amblygaster sirm at two landing sites in Tanga on the northern coast of Tanzania. Fish samples were collected on a monthly basis from ringnets operated by artisanal fishers in the nearby coastal waters. Spawning seasons were determined using gonadosomatic index (GSI) and gonadal maturity stages. The size at first maturity was 57.7 mm and 66.2 mm total length for male and female S. commersonnii respectively. Male and female A. sirm were estimated to attain first maturity at 147.7 mm and 169.2 mm respectively. The spawning seasons of both species were protracted. S. commersonnii demonstrated a year round spawning cycle with peaks in August, October and January. The peak spawning season for male and female A. sirm was recorded in August and September respectively. Both species exhibited skewed size-dependent sex ratios with females predominating in the larger size classes. A. sirm had a higher fecundity rate with a maximum of 96,500 eggs in the largest female fish of 258 mm as compared to S. commersonnii (10,055 eggs) in the largest fish of 98 mm. The mean (±SE) total fecundity of S. comersonnii and A. sirm was 5,134.7 ± 136.9 eggs, and 47,029.03 ± 1,435.13 eggs in females of sizes 68 mm to 98 mm and 170 mm to 258 mm respectively.

Preliminary findings on the food and feeding dynamics of the anchovy Stolephorus commersonnii (Lacepède, 1803) and the Indian mackerel Rastrelliger kanagurta (Cuvier, 1817) from Tanga Region, Tanzania - Baraka C. Sekadende; Joseph S. Sululu; Albogast T. Kamukuru; Mathias M. Igulu; Shigalla B. Mahongo (Western Indian Ocean Journal of Marine Science, 2021)
Small pelagic fishes play an important role in the ecosystem by linking planktonic production and higher trophic level predators, and provide a livelihood to both the small-scale and commercial fisher communities. This study analyzed the food and feeding habits of Stolephorus commersonnii (Lacepède, 1803) and Rastrelliger kanagurta (Cuvier, 1817) from the ring-net fishery in Tanga, Tanzania. A total of 1 434 and 320 stomachs of S. commersonnii and R. kanagurta respectively were examined for gut contents using the relative volumetric method. S. commersonnii was found to be a planktivorous carnivore, feeding principally on planktonic penaeid shrimps (48.6%), fish larvae (33.2%) and zooplankton (12.3%). R. kanagurta was found to be carnivorous, feeding predominantly on fish (60.6%), mainly S. commersonnii, while penaeid shrimps, juvenile fish, and juvenile stages of squids formed 26.5% of the total number of food items in R. kanagurta guts. Both S. commersonnii and R. kanagurta exhibited ontogenic diet shifts, where they fed exclusively on small prey as juveniles and consumed larger food items as they grew. The index of vacuity was higher in S. commersonnii (46.1%) than in R. kanagurta (16.6%). This study revealed the importance of penaeid shrimps as food for S. commersonnii, that in turn formed the main food for R. kanagurta. This implied that the two species were able to coexist in the same niche by avoiding interspecific competition for food.

Extreme Levels of Ocean Acidification Restructure the Plankton Community and Biogeochemistry of a Temperate Coastal Ecosystem: A Mesocosm Study - Carsten Spisla; Jan Taucher; Lennart T. Bach; Mathias Haunost; Tim Boxhammer; Andrew L. King; Bettany D. Jenkins; Joselynn R. Wallace; Andrea Ludwig; Jana Meyer; Paul Stange; Fabrizio Minutolo; et al. (Frontiers in Marine Science, 2021)
The oceans’ uptake of anthropogenic carbon dioxide (CO 2 ) decreases seawater pH and alters the inorganic carbon speciation – summarized in the term ocean acidification (OA). Already today, coastal regions experience episodic pH events during which surface layer pH drops below values projected for the surface ocean at the end of the century. Future OA is expected to further enhance the intensity of these coastal extreme pH events. To evaluate the influence of such episodic OA events in coastal regions, we deployed eight pelagic mesocosms for 53 days in Raunefjord, Norway, and enclosed 56–61 m 3 of local seawater containing a natural plankton community under nutrient limited post-bloom conditions. Four mesocosms were enriched with CO 2 to simulate extreme p CO 2 levels of 1978 – 2069 μatm while the other four served as untreated controls. Here, we present results from multivariate analyses on OA-induced changes in the phyto-, micro-, and mesozooplankton community structure. Pronounced differences in the plankton community emerged early in the experiment, and were amplified by enhanced top-down control throughout the study period. The plankton groups responding most profoundly to high CO 2 conditions were cyanobacteria (negative), chlorophyceae (negative), auto- and heterotrophic microzooplankton (negative), and a variety of mesozooplanktonic taxa, including copepoda (mixed), appendicularia (positive), hydrozoa (positive), fish larvae (positive), and gastropoda (negative). The restructuring of the community coincided with significant changes in the concentration and elemental stoichiometry of particulate organic matter. Results imply that extreme CO 2 events can lead to a substantial reorganization of the planktonic food web, affecting multiple trophic levels from phytoplankton to primary and secondary consumers.

Whole genome sequencing and phylogenetic classification of Tunisian SARS-CoV-2 strains from patients of the Military Hospital in Tunis - Susann Handrick; Malena Bestehorn-Willmann; Simone Eckstein; Mathias C. Walter; Markus H. Antwerpen; Habiba Naija; Kilian Stoecker; Roman Wölfel; Mohamed Ben Moussa (Virus Genes, 2020)
In the present work, two complete genome sequences of SARS-CoV-2 were obtained from nasal swab samples of Tunisian SARS-CoV-2 PCR-positive patients using nanopore sequencing. The virus genomes of two of the patients examined, a Tunisian soldier returning from a mission in Morocco and a member of another Tunisian family, showed significant differences in analyses of the total genome and single nucleotide polymorphisms (SNPs). Phylogenetic relationships with known SARS-CoV-2 genomes in the African region, some European and Middle Eastern countries and initial epidemiological conclusions indicate that the introduction of SARS-CoV-2 into Tunisia from two independent sources was travel-related.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Use of acoustics to enhance the efficiency of physical screens designed to protect downstream moving European eel ( Anguilla anguilla ) - Mathias J. C. Deleau; Paul R. White; Graeme Peirson; Timothy G. Leighton; Paul S. Kemp (Fisheries Management and Ecology, 2020)
European eel, Anguilla anguilla (L.), is vulnerable to entrainment at a variety of man‐made intakes, including those that lead to hydropower turbines or other abstraction points. Two experiments were conducted to investigate the potential for acoustic stimuli to improve the efficiency of a vertical bar screen to guide downstream moving eel. Three underwater speakers were installed along the channel wall of an external flume, upstream of the screen. In the first experiment (a), screen guidance efficiency recorded in the presence (treatment) and absence (control) of a continuous broadband stimulus was individually compared between fish from two respective groups. Adopting a “before‐after” design, the second experiment (b) assessed individually the guidance of control eels from the group previously used in experiment 1 when exposed to a 100 Hz pulse. The majority of eels reached the bypass in both experiments with only three passing through the screen during the controls against one during each acoustic treatment. Rejection of the area adjacent to the speakers was more common during the acoustic treatment, with eels moving past the speakers more rapidly in the presence of sound. The results suggest that employing acoustic stimuli enhances the guidance efficiency of physical screens.

Broad‐front migration leads to strong migratory connectivity in the lesser kestrel ( Falco naumanni ) - Maurizio Sarà; Salvatore Bondì; Ana Bermejo; Mathieu Bourgeois; Mathias Bouzin; Javier Bustamante; Javier de la Puente; Angelos Evangelidis; Annagrazia Frassanito; Egidio Fulco; Giuseppe Giglio; Gradimir Gradev; et al. (Journal of Biogeography, 2019)
Aim Migratory animals regularly move between often distant breeding and non‐breeding ranges. Knowledge about how these ranges are linked by movements of individuals from different populations is crucial for unravelling temporal variability in population spatial structuring and for identifying environmental drivers of population dynamics acting at different spatio‐temporal scales. We performed a large‐scale individual‐based migration tracking study of an Afro‐Palaearctic migratory raptor, to determine the patterns of migratory connectivity of European breeding populations. Location Europe, Africa. Methods Migration data were recorded using different devices (geolocators, satellite transmitters, Global Positioning System dataloggers) from 87 individuals breeding in the three core European populations, located in the Iberian, Italian and Balkan peninsulas. We estimated connectivity by the Mantel correlation coefficient ( r M ), and computed both the degree of separation between the non‐breeding areas of individuals from the same population (i.e. the population spread) and the relative size of the non‐breeding range (i.e. the non‐breeding range spread). Results European lesser kestrels migrated on a broad front across the Mediterranean Sea and Sahara Desert, with different populations using different routes. Iberian birds migrated to western Sahel (Senegal, Mauritania, western Mali), Balkan birds migrated chiefly to central‐eastern Sahel (Niger, Nigeria, Chad), whereas Italian ones spread from eastern Mali to Nigeria. Spatial differentiation of non‐breeding areas led to a strong migratory connectivity ( r M = .58), associated with a relatively high population (637 km) and non‐breeding range (1,149 km) spread. Main conclusions Our comprehensive analysis of the non‐breeding distribution of European lesser kestrel populations revealed a strong migratory connectivity, a rare occurrence in long‐distance avian migrants. The geographical conformation of the species’ breeding and non‐breeding ranges, together with broad‐front migration across ecological barriers, promoted the differentiation of migratory routes and non‐breeding areas. Strong connectivity could then arise because of both high population spread and broad non‐breeding range.

Klotho Is Neuroprotective in the Superoxide Dismutase (SOD1G93A) Mouse Model of ALS - Ella Zeldich; Ci-Di Chen; Emma Boden; Bryce Howat; Jason S. Nasse; Dean Zeldich; Anthony G. Lambert; Andrea Yuste; Jonathan D. Cherry; Rebecca M. Mathias; Qicheng Ma; Nelson C. Lau; et al. (Journal of Molecular Neuroscience, 2019)

Differences in smolt status affect the resistance of Atlantic salmon ( Salmo salar L.) against infectious pancreatic necrosis, while vaccine‐mediated protection is unaffected - Ingvill Jensen; Mathias C. Overrein; Børge N. Fredriksen; Guro Strandskog; Tore Seternes (Journal of Fish Diseases, 2019)
In today's aquaculture of Atlantic salmon ( Salmo salar L.), a majority of viral disease outbreaks occur after seawater transfer. A relevant question is how the parr–smolt transformation influences the efficacy of viral vaccines and the innate resistance against viral diseases. In this study, vaccinated and unvaccinated A. salmon parr were exposed to different photoperiodic regimens (1‐, 3‐ or 6‐week continuous light—WCL). Fish groups at different stages in the smoltification process were induced, as demonstrated by differences in morphological and physiological smolt parameters. At the time of seawater transfer, the 6‐WCL group had reached a more pronounced stage in the smoltification process than the 1‐WCL group. In unvaccinated fish, the subsequent cohabitation challenge with infectious pancreatic necrosis virus (IPNV) gave a significantly higher accumulated mortality in the 6‐WCL group (87%) compared to the 1‐WCL group (39%). In the vaccinated groups, this effect was not apparent and there were no differences in accumulated mortality between the 1 WCL, 3 WCL and 6‐WCL groups. These data suggest that the resistance to IPN in A. salmon was negatively influenced by smoltification, while vaccine‐mediated protection to IPN was maintained equally well irrespective of smolt status.

Joint species distribution models with species correlations and imperfect detection - Mathias W. Tobler; Marc Kéry; Francis K. C. Hui; Gurutzeta Guillera‐Arroita; Peter Knaus; Thomas Sattler (Ecology, 2019)
Spatiotemporal patterns in biological communities are typically driven by environmental factors and species interactions. Spatial data from communities are naturally described by stacking models for all species in the community. Two important considerations in such multispecies or joint species distribution models ( JSDM s) are measurement errors and correlations between species. Up to now, virtually all JSDM s have included either one or the other, but not both features simultaneously, even though both measurement errors and species correlations may be essential for achieving unbiased inferences about the distribution of communities and species co‐occurrence patterns. We developed two presence–absence JSDM s for modeling pairwise species correlations while accommodating imperfect detection: one using a latent variable and the other using a multivariate probit approach. We conducted three simulation studies to assess the performance of our new models and to compare them to earlier latent variable JSDM s that did not consider imperfect detection. We illustrate our models with a large Atlas data set of 62 passerine bird species in Switzerland. Under a wide range of conditions, our new latent variable JSDM with imperfect detection and species correlations yielded estimates with little or no bias for occupancy, occupancy regression coefficients, and the species correlation matrix. In contrast, with the multivariate probit model we saw convergence issues with large data sets (many species and sites) resulting in very long run times and larger errors. A latent variable model that ignores imperfect detection produced correlation estimates that were consistently negatively biased, that is, underestimated. We found that the number of latent variables required to represent the species correlation matrix adequately may be much greater than previously suggested, namely around n /2, where n is community size. The analysis of the Swiss passerine data set exemplifies how not accounting for imperfect detection will lead to negative bias in occupancy estimates and to attenuation in the estimated covariate coefficients in a JSDM . Furthermore, spatial heterogeneity in detection may cause spurious patterns in the estimated species correlation matrix if not accounted for. Our new JSDM s represent an important extension of current approaches to community modeling to the common case where species presence–absence cannot be detected with certainty.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

How invasive oysters can affect parasite infection patterns in native mussels on a large spatial scale - M. Anouk Goedknegt; Reinier Nauta; Mirjana Markovic; Christian Buschbaum; Eelke O. Folmer; Pieternella C. Luttikhuizen; Jaap van der Meer; Andreas M. Waser; K. Mathias Wegner; David W. Thieltges (Oecologia, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Scalar-Flux Similarity in the Layer Near the Surface Over Mountainous Terrain - Eleni Sfyri; Mathias W. Rotach; Ivana Stiperski; Fred C. Bosveld; Manuela Lehner; Friedrich Obleitner (Boundary-Layer Meteorology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Multiple perspectives on the attribution of the extreme European summer of 2012 to climate change - Laura J. Wilcox; Pascal Yiou; Mathias Hauser; Fraser C. Lott; Geert Jan van Oldenborgh; Ioana Colfescu; Buwen Dong; Gabi Hegerl; Len Shaffrey; Rowan Sutton (Climate Dynamics, 2018)

Signature of postglacial colonization on contemporary genetic structure and diversity of Quadrula quadrula (Bivalvia: Unionidae) - Philip T. Mathias; Jordan R. Hoffman; Chris C. Wilson; David T. Zanatta (Hydrobiologia, 2018)

Dual transcriptomics reveals co‐evolutionary mechanisms of intestinal parasite infections in blue mussels Mytilus edulis - Marieke E. Feis; Uwe John; Ana Lokmer; Pieternella C. Luttikhuizen; K. Mathias Wegner (Molecular Ecology, 2018)
On theoretical grounds, antagonistic co‐evolution between hosts and their parasites should be a widespread phenomenon but only received little empirical support so far. Consequently, the underlying molecular mechanisms and evolutionary steps remain elusive, especially in nonmodel systems. Here, we utilized the natural history of invasive parasites to document the molecular underpinnings of co‐evolutionary trajectories. We applied a dual‐species transcriptomics approach to experimental cross‐infections of blue mussel Mytilus edulis hosts and their invasive parasitic copepods Mytilicola intestinalis from two invasion fronts in the Wadden Sea. We identified differentially regulated genes from an experimental infection contrast for hosts (infected vs. control) and a sympatry contrast (sympatric vs. allopatric combinations) for both hosts and parasites. The damage incurred by Mytilicola infection and the following immune response of the host were mainly reflected in cell division processes, wound healing, apoptosis and the production of reactive oxygen species ( ROS ). Furthermore, the functional coupling of host and parasite sympatry contrasts revealed the concerted regulation of chitin digestion by a Chitotriosidase 1 homolog in hosts with several cuticle proteins in the parasite. Together with the coupled regulation of ROS producers and antagonists, these genes represent candidates that mediate the different evolutionary trajectories within the parasite's invasion. The host–parasite combination‐specific coupling of these effector mechanisms suggests that underlying recognition mechanisms create specificity and local adaptation. In this way, our study demonstrates the use of invasive species’ natural history to elucidate molecular mechanisms of host–parasite co‐evolution in the wild.

The Oxygen Paradox, the French Paradox, and age-related diseases - Joanna M. S. Davies; Josiane Cillard; Bertrand Friguet; Enrique Cadenas; Jean Cadet; Rachael Cayce; Andrew Fishmann; David Liao; Anne-Laure Bulteau; Frédéric Derbré; Amélie Rébillard; Steven Burstein; et al. (GeroScience, 2017)

Gradient-based production optimization with simulation-based economic constraints - Oleg Volkov; Mathias C. Bellout (Computational Geosciences, 2017)

Glycoprotein-G-gene-based molecular and phylogenetic analysis of rabies viruses associated with a large outbreak of bovine rabies in southern Brazil - Juliana F. Cargnelutti; João M. de Quadros; Mathias Martins; Helena B. C. R. Batista; Rudi Weiblen; Eduardo F. Flores (Archives of Virology, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Phosphorus levels determine changes in growth and biochemical composition of Chlorella vulgaris during cadmium stress - Mathias Ahii Chia; Ana Teresa Lombardi; Maria da Graça G. Melão; Christopher C. Parrish (Journal of Applied Phycology, 2017)

Effect of Loss of Heart Rate Variability on T-Wave Heterogeneity and QT Variability in Heart Failure Patients: Implications in Ventricular Arrhythmogenesis - Sachin Nayyar; Muhammad A. Hasan; Kurt C. Roberts-Thomson; Thomas Sullivan; Mathias Baumert (Cardiovascular Engineering and Technology, 2017)

Attenuation of Axonal Degeneration by Calcium Channel Inhibitors Improves Retinal Ganglion Cell Survival and Regeneration After Optic Nerve Crush - Vinicius T. Ribas; Jan C. Koch; Uwe Michel; Mathias Bähr; Paul Lingor (Molecular Neurobiology, 2017)

Spillover but no spillback of two invasive parasitic copepods from invasive Pacific oysters (Crassostrea gigas) to native bivalve hosts - M. Anouk Goedknegt; Anne-Karin Schuster; Christian Buschbaum; René Gergs; A. Sarina Jung; Pieternella C. Luttikhuizen; Jaap van der Meer; Karin Troost; K. Mathias Wegner; David W. Thieltges (Biological Invasions, 2017)

Antimicrobial binding and growth kinetics in BacT/ALERT® FA Plus and BACTEC® Aerobic/F Plus blood culture media - D. Lovern; B. Katzin; K. Johnson; D. Broadwell; E. Miller; A. Gates; P. Deol; K. Doing; A. van Belkum; C. Marshall; E. Mathias; W. M. Dunne (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Well placement optimization subject to realistic field development constraints - Mansoureh Jesmani; Mathias C. Bellout; Remus Hanea; Bjarne Foss (Computational Geosciences, 2016)

Retinal and Optic Nerve Damage is Associated with Early Glial Responses in an Experimental Autoimmune Glaucoma Model - Rozina Noristani; Sandra Kuehn; Gesa Stute; Sabrina Reinehr; Mathias Stellbogen; H. Burkhard Dick; Stephanie C. Joachim (Journal of Molecular Neuroscience, 2016)

Social network dynamics: the importance of distinguishing between heterogeneous and homogeneous changes - Mathias Franz; Susan C. Alberts (Behavioral Ecology and Sociobiology, 2015)

Quantifying landscape‐level methane fluxes in subarctic Finland using a multiscale approach - Iain. P. Hartley; Timothy. C. Hill; Thomas. J. Wade; Robert. J. Clement; John. B. Moncrieff; Ana. Prieto‐Blanco; Mathias. I. Disney; Brian. Huntley; Mathew. Williams; Nicholas. J. K. Howden; Philip. A. Wookey; Robert. Baxter (Global Change Biology, 2015)
Quantifying landscape‐scale methane ( CH 4 ) fluxes from boreal and arctic regions, and determining how they are controlled, is critical for predicting the magnitude of any CH 4 emission feedback to climate change. Furthermore, there remains uncertainty regarding the relative importance of small areas of strong methanogenic activity, vs. larger areas with net CH 4 uptake, in controlling landscape‐level fluxes. We measured CH 4 fluxes from multiple microtopographical subunits (sedge‐dominated lawns, interhummocks and hummocks) within an aapa mire in subarctic Finland, as well as in drier ecosystems present in the wider landscape, lichen heath and mountain birch forest. An intercomparison was carried out between fluxes measured using static chambers, up‐scaled using a high‐resolution landcover map derived from aerial photography and eddy covariance. Strong agreement was observed between the two methodologies, with emission rates greatest in lawns. CH 4 fluxes from lawns were strongly related to seasonal fluctuations in temperature, but their floating nature meant that water‐table depth was not a key factor in controlling CH 4 release. In contrast, chamber measurements identified net CH 4 uptake in birch forest soils. An intercomparison between the aerial photography and satellite remote sensing demonstrated that quantifying the distribution of the key CH 4 emitting and consuming plant communities was possible from satellite, allowing fluxes to be scaled up to a 100 km 2 area. For the full growing season (May to October), ~ 1.1–1.4 g CH 4 m −2 was released across the 100 km 2 area. This was based on up‐scaled lawn emissions of 1.2–1.5 g CH 4 m −2 , vs. an up‐scaled uptake of 0.07–0.15 g CH 4 m −2 by the wider landscape. Given the strong temperature sensitivity of the dominant lawn fluxes, and the fact that lawns are unlikely to dry out, climate warming may substantially increase CH 4 emissions in northern Finland, and in aapa mire regions in general.

The effect of pH on fatigue during submaximal isometric contractions of the human calf muscle - Jason C. Siegler; Paul Marshall; Mathias K. Pouslen; Niels-Peter B. Nielsen; David Kennedy; Simon Green (European Journal of Applied Physiology, 2015)

Foliar elemental composition of E uropean forest tree species associated with evolutionary traits and present environmental and competitive conditions - Jordi Sardans; Ivan A. Janssens; Rocio Alonso; Stavros D. Veresoglou; Mathias C. Rillig; Tanja GM Sanders; Jofre Carnicer; Iolanda Filella; Gerard Farré‐Armengol; Josep Peñuelas (Global Ecology and Biogeography, 2015)
Aim Plant elemental composition and stoichiometry are crucial for plant structure and function. We studied to what extent elemental stoichiometry in plants might be strongly related to environmental drivers and competition from coexisting species. Location Europe. Methods We analysed foliar N , P , K , C a and M g concentrations and their ratios among 50 species of E uropean forest trees sampled in 5284 plots across E urope and their relationships with phylogeny, forest type, current climate and N deposition. Results Phylogeny is strongly related to overall foliar elemental composition in European tree species. Species identity explained 56.7% of the overall foliar elemental composition and stoichiometry. Forest type and current climatic conditions also partially explained the differences in foliar elemental composition among species. In the same genus co‐occurring species had overall higher differences in foliar elemental composition and stoichiometry than the non‐co‐occurring species. Main conclusions The different foliar elemental compositions among species are related to phylogenetic distances, but they are also related to current climatic conditions, forest types, drivers of global change such as atmospheric N deposition, and to differences among co‐occurring species as a probable consequence of niche specialization to reduce direct competition for the same resources. Different species have their own ‘fixed’ foliar elemental compositions but retain some degree of plasticity to the current climatic and competitive conditions. A wider set of elements beyond N and P better represent the biogeochemical niche and are highly sensitive to plant function. Foliar elemental composition can thus be useful for representing important aspects of plant species niches.

Sperm Bundles in the Seminal Vesicle of the Crematogaster victima (Smith) Adult Males (Hymenoptera: Formicidae) - C M Oliveira; J Moreira; L F Gomes; M I Camargo-Mathias; J Lino-Neto (Neotropical Entomology, 2014)

Understanding the biology of ex vivo-expanded CD8 T cells for adoptive cell therapy: role of CD62L - C. Marcela Díaz-Montero; Abdel-Aziz Zidan; Maria F. Pallin; Vasileios Anagnostopoulos; Mohamed L. Salem; Eric Wieder; Krishna Komanduri; Alberto J. Montero; Mathias G. Lichtenheld (Immunologic Research, 2013)

Diggin′ on U(biquitin): A Novel Method for the Identification of Physiological E3 Ubiquitin Ligase Substrates - Carrie E. Rubel; Jonathan C. Schisler; Eric D. Hamlett; Robert M. DeKroon; Mathias Gautel; Oscar Alzate; Cam Patterson (Cell Biochemistry and Biophysics, 2013)

Mammary gland development is delayed in mice deficient for aminopeptidase N - Andreas F. Kolb; David Sorrell; Caroline Lassnig; Simon Lillico; Ailsa Carlisle; Claire Neil; Claire Robinson; Mathias Müller; C. Bruce A. Whitelaw (Transgenic Research, 2013)

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD - Nadia N. Hansel; Ingo Ruczinski; Nicholas Rafaels; Don D. Sin; Denise Daley; Alla Malinina; Lili Huang; Andrew Sandford; Tanda Murray; Yoonhee Kim; Candelaria Vergara; Susan R. Heckbert; et al. (Human Genetics, 2013)

Modelling of riverine ecosystems by integrating models: conceptual approach, a case study and research agenda - Sonja C. Jähnig; Mathias Kuemmerlen; Jens Kiesel; Sami Domisch; Qinghua Cai; Britta Schmalz; Nicola Fohrer (Journal of Biogeography, 2012)
Aim Highly complex interactions between the hydrosphere and biosphere, as well as multifactorial relationships, characterize the interconnecting role of streams and rivers between different elements of a landscape. Applying species distribution models ( SDM s) in these ecosystems requires special attention because rivers are linear systems and their abiotic and biotic conditions are structured in a linear fashion with significant influences from upstream/downstream or lateral influences from adjacent areas. Our aim was to develop a modelling framework for benthic invertebrates in riverine ecosystems and to test our approach in a data‐rich study catchment. Location We present a case study of a 9‐km section of the lowland K ielstau R iver located in northern G ermany. Methods We linked hydrological, hydraulic and species distribution models to predict the habitat suitability for the bivalve S phaerium corneum in a riverine system. The results generated by the hydrological model served as inputs into the hydraulic model, which was used to simulate the resulting water levels, velocities and sediment discharge within the stream channel. Results The ensemble model obtained good evaluation scores (area under the receiver operating characteristic curve 0.96; kappa 0.86; true skill statistic 0.95; sensitivity 86.14; specificity 85.75). Mean values for variables at the sampling sites were not significantly different from the values at the predicted distribution ( M ann– W hitney U ‐test P > 0.05). High occurrence probabilities were predicted in the downstream half of the 9‐km section of the K ielstau. The most important variable for the model was sediment discharge (contributing 40%), followed by water depth (30%), flow velocity (19%) and stream power (11%). Main conclusions The hydrological and hydraulic models are able to produce predictors, acting at different spatial scales, which are known to influence riverine organisms; which, in turn, are used by the SDM s as input. Our case study yielded good results, which corresponded well with ecological knowledge about our study organism. Although this method is feasible for making projections of habitat suitability on a local scale (here: a reach in a small catchment), we discuss remaining challenges for future modelling approaches and large‐scale applications.

Joint optimization of oil well placement and controls - Mathias C. Bellout; David Echeverría Ciaurri; Louis J. Durlofsky; Bjarne Foss; Jon Kleppe (Computational Geosciences, 2012)

Axonal degeneration as a therapeutic target in the CNS - Paul Lingor; Jan C. Koch; Lars Tönges; Mathias Bähr (Cell and Tissue Research, 2012)

Europrotomus (Mollusca: Caenogastropoda: Strombidae): a new Middle Miocene European strombid genus (Revision of Euprotomus Gill, 1870. Part 4) - Gijs C. Kronenberg; Mathias Harzhauser (PalZ, 2012)

(2-Methoxyethoxy)acetic acid: a urinary biomarker of exposure for jet fuel JP-8 - Clayton B’Hymer; Patricia Mathias; Edward Krieg; Kenneth L. Cheever; Christine A. Toennis; John C. Clark; James S. Kesner; Roger L. Gibson; Mary Ann Butler (International Archives of Occupational and Environmental Health, 2012)

Toxicity, dioxin-like activities, and endocrine effects of DDT metabolites—DDA, DDMU, DDMS, and DDCN - Bernhard Wetterauer; Mathias Ricking; Jens C. Otte; Arnold V. Hallare; Andrew Rastall; Lothar Erdinger; Jan Schwarzbauer; Thomas Braunbeck; Henner Hollert (Environmental Science and Pollution Research, 2012)

A Critical Re-Examination of the Intraluminal Filament MCAO Model: Impact of External Carotid Artery Transection - Rebecca C. Trueman; David J. Harrison; Dominic M. Dwyer; Stephen B. Dunnett; Mathias Hoehn; Tracy D. Farr (Translational Stroke Research, 2011)

Down-regulation of CK2 activity results in a decrease in the level of cdc25C phosphatase in different prostate cancer cell lines - Carolin C. Schneider; Claudia Götz; Andrea Hessenauer; Jürgen Günther; Sabine Kartarius; Mathias Montenarh (Molecular and Cellular Biochemistry, 2011)

Early life stress paradigms in rodents: potential animal models of depression? - Mathias V. Schmidt; Xiao-Dong Wang; Onno C. Meijer (Psychopharmacology, 2011)

“Hot standards” for the thermoacidophilic archaeon Sulfolobus solfataricus - Melanie Zaparty; Dominik Esser; Susanne Gertig; Patrick Haferkamp; Theresa Kouril; Andrea Manica; Trong K. Pham; Julia Reimann; Kerstin Schreiber; Pawel Sierocinski; Daniela Teichmann; Marleen van Wolferen; et al. (Extremophiles, 2010)

Molecular insights into the colonization and chromosomal diversification of Madeiran house mice - D. W. FÖRSTER; İ. GÜNDÜZ; A. C. NUNES; S. GABRIEL; M. G. RAMALHINHO; M. L. MATHIAS; J. BRITTON‐DAVIDIAN; J. B. SEARLE (Molecular Ecology, 2009)
The colonization history of Madeiran house mice was investigated by analysing the complete mitochondrial (mt) D‐loop sequences of 156 mice from the island of Madeira and mainland Portugal, extending on previous studies. The numbers of mtDNA haplotypes from Madeira and mainland Portugal were substantially increased (17 and 14 new haplotypes respectively), and phylogenetic analysis confirmed the previously reported link between the Madeiran archipelago and northern Europe. Sequence analysis revealed the presence of four mtDNA lineages in mainland Portugal, of which one was particularly common and widespread (termed the ‘Portugal Main Clade’). There was no support for population bottlenecks during the formation of the six Robertsonian chromosome races on the island of Madeira, and D‐loop sequence variation was not found to be structured according to karyotype. The colonization time of the Madeiran archipelago by Mus musculus domesticus was approached using two molecular dating methods (mismatch distribution and Bayesian skyline plot). Time estimates based on D‐loop sequence variation at mainland sites (including previously published data from France and Turkey) were evaluated in the context of the zooarchaeological record of M. m. domesticus. A range of values for mutation rate (μ) and number of mouse generations per year was considered in these analyses because of the uncertainty surrounding these two parameters. The colonization of Portugal and Madeira by house mice is discussed in the context of the best‐supported parameter values. In keeping with recent studies, our results suggest that mutation rate estimates based on interspecific divergence lead to gross overestimates concerning the timing of recent within‐species events.

Nanotechnology approaches for gene transfer - Karin E. Lundin; Oscar E. Simonson; Pedro M. D. Moreno; Eman M. Zaghloul; Iulian I. Oprea; Mathias G. Svahn; C. I. Edvard Smith (Genetica, 2009)

Effect of verapamil on tachycardia-induced early cellular electrical remodeling in rabbit atrium - Roman Laszlo; Christoph Winkler; Stefan Wöhrl; Ralf E. Wessel; Sara Laszlo; Mathias C. Busch; Jürgen Schreieck; Ralph F. Bosch (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Growth/climate response shift in a long subalpine spruce chronology - Ulf Büntgen; David C. Frank; Martin Schmidhalter; Burkhard Neuwirth; Mathias Seifert; Jan Esper (Trees, 2006)

Light Measurement Methods Related to Forage Yield in a Grazed Northern Conifer Silvopasture in the Appalachian Region of Eastern USA - C. M. Feldhake; J. P. S. Neel; D. P. Belesky; E. L. Mathias (Agroforestry Systems, 2005)

Influence of physical environmental characteristics and anthropogenic factors on the position and structure of a contact zone between two chromosomal races of the house mouse on the island of Madeira (North Atlantic, Portugal) - A. C. Nunes; J. Britton‐Davidian; J. Catalan; M. G. Ramalhinho; R. Capela; M. L. Mathias; G. Ganem (Journal of Biogeography, 2005)
Aim This study aimed to investigate if and how environmental characteristics (physical factors of the natural environment and the human impact on the landscape) influence the position and structure of a contact zone between two chromosomal races of the house mouse ( Mus musculus domesticus Rutty 1712) from the island of Madeira. Location The western part of Madeira, a volcanic island in the North Atlantic. Methods Mice were sampled along a south/north‐western transect following the main road, in human‐modified outdoor habitats. Karyotypes of mice were determined using the yeast‐stimulated bone marrow cell method. Trapping sites were characterized in terms of their physical (altitude, temperature, precipitation and soil type) and habitat (human landscape use and occupancy) features. Demographic parameters of mouse populations, based on trapping‐with‐removal techniques, were also analysed (relative abundance, sex‐ratio, juvenile ratio and female fertility ratio), as well as body size (weight and length). Results Four chromosomal zones were identified on the basis of the frequency of two diagnostic rearrangements (Rb(6.7) in race E. Calheta and Rb(7.15) in race A. Cruz). E. Calheta was present in the two southern‐most zones, followed by the contact zone characterized by the presence of two inter‐racial hybrids and the co‐occurrence of mice belonging to the two races. The northern‐most part of the transect was occupied by A. Cruz. Environmental features differed leading us to split the transect into two parts. The southern part is characterized by lower altitude and precipitation, milder temperature, better soil quality supporting vegetable crops and vineyards, and more abundant and evenly distributed human habitats. This southern part is occupied by E. Calheta mice. The north‐western part presents characteristics opposite to those described above with cereals as the main cultivated crop, and it includes the contact zone as well as the zone inhabited by A. Cruz mice. The demographic parameters evaluated in this study did not differ significantly between chromosomal zones. Main conclusions This ecological survey highlights differences in climatic and edaphic features that have moulded the agricultural activities of humans, contributing to a differentiation of their spatial development, and hence the structure of potential habitats for mice. Results are interpreted within the source–sink framework of population dynamics, following which E. Calheta may function as a source and the areas where A. Cruz and the contact zone are located may function as a sink. Our study suggests that the position and chromosomal composition of the contact zone is influenced by the human component underlying broader environmental features. Similar characteristics were most likely present during the historical settlement of Madeira. They may have favoured the independent divergence of the two races and influenced the dynamics of the contact zone.

Sensitivity of macroecological patterns of South American parrots to differences in data sources - Pablo V. C. Mathias; Cláudio V. Mendonça; Thiago F. L. V. B. Rangel; José A. F. Diniz‐Filho (Global Ecology and Biogeography, 2004)
A criticism of macroecological studies has been their extensive use of secondary data sources. In this note we evaluate how different data sources affect macroecological patterns for the parrots of South America. We mapped extents of parrot occurrence based on four sources of range maps. We compared basic statistics for geographical range size distribution (mean, variance and skew) and calculated correlations between geographical range size estimates and grid cell species richness estimates. Finally, results from multiple regression analyses of species richness against six environmental variables were also compared. We found that patterns were very robust to the data source, with only relatively slight quantitative differences. Our results reinforce the notion that patterns emerging from macroecological analyses are robust to variations in data sources and cannot be merely artefacts resulting from low data quality, notably poorly defined mapping and conflicting taxonomy.

Effects of carvedilol on oxidative stress in human endothelial cells and healthy volunteers - Dimitrios Tsikas; Christina Mehls; Rainer H. Bger; Jrgen C. Frlich; Dirk O. Stichtenoth; Frank-Mathias Gutzki; Stefanie A. Fahlbusch (European Journal of Clinical Pharmacology, 2004)

Evidence for asthma susceptibility genes on chromosome 11 in an African-American population - Shau-Ku Huang; Rasika A. Mathias; Eva Ehrlich; Beverly Plunkett; Xin Liu; Garry R. Cutting; Xin-Jing Wang; Xiao-Dong Li; Alkis Togias; Kathleen C. Barnes; Floyd Malveaux; Stephen Rich; et al. (Human Genetics, 2003)

Developmental Instability in a Riparian Population of the Algerian Mouse(Mus spretus) Associated with a Heavy Metal–Polluted Area in Central Portugal - A. C. Nunes; J.-C. Auffray; M. L. Mathias (Archives of Environmental Contamination and Toxicology, 2001)

Molecular studies on the colonization of the Madeiran archipelago by house mice - İ. GÜndüz; J.‐C. Auffray; J. Britton‐Davidian; J. Catalan; G. Ganem; M. G. Ramalhinho; M. L. Mathias; J. B. Searle (Molecular Ecology, 2001)
To study the colonization history of the house mouse ( Mus musculus domesticus ) on the Madeiran archipelago, complete mitochondrial D‐ loop sequences were obtained for 44 individuals from Madeira, Porto Santo and Ilhas Desertas. Altogether, 19 D‐ loop haplotypes were identified which formed part of a single clade in a phylogeny incorporating haplotypes from elsewhere in the range of M. m. domesticus , indicating that the Madeiras were colonized from a single source. Similarities between the sequences found in the Madeiras and those in Scandinavia and northern Germany suggest that northern Europe was the source area, and there is the intriguing possibility that the Vikings may have accidentally brought house mice to the archipelago. However, there is no record of Vikings visiting the Madeiras; on historical grounds, Portugal is the most likely source area for Madeiran mice and further molecular data from Portugal are needed to rule out that possibility.

The Role of MIP in Lens Fiber Cell Membrane Transport - K. Varadaraj; C. Kushmerick; G.J. Baldo; S. Bassnett; A. Shiels; R.T. Mathias (The Journal of Membrane Biology, 1999)

Effects of Lens Major Intrinsic Protein on Glycerol Permeability and Metabolism - C. Kushmerick; K. Varadaraj; R.T. Mathias (The Journal of Membrane Biology, 1998)

Somatic embryogenesis and plant regeneration from stem explants of Moricandia arvensis - W. Craig; A. Wiegand; C. M. O'Neill; R. J. Mathias; J. B. Power; M. R. Davey (Plant Cell Reports, 1997)

Moderate exercise leads to decreased expression of ?1 and ?2 integrins on leucocytes - Jens Jordan; Ralph Beneke; Mathias Htler; Alexander Veith; Hermann Haller; Friedrich C. Luft (European Journal of Applied Physiology, 1997)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)